Improving SME Performance in Salatiga City: Integrating Islamic Leadership and Innovation Models - Yudha Trishananto; Esa Dilla Maulani; Dinda Inti Nur Arianti; Ulfah Nurul Fauziah (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to examine the relationship between Islamic leadership, innovation, and performance of small and medium enterprises (SMEs) in Indonesia, especially in the city of Salatiga. In this study, the main research is on innovation as a mediation between Islamic leadership and SME performance. The population in this study were all SMEs in the city of Salatiga with a sample of 100 respondents. The tool used to analyze the data in this study used SPSS version 24. Sobel test was used to test whether the variables could mediate or not. This study concludes that Islamic leadership has a direct effect on the performance of SMEs and innovation, innovation has a direct effect on the performance of SMEs, and innovation can mediate the relationship between Islamic leadership and SME performance. The originality of this study is the mediating effect of innovation in the relationship between Islamic leadership and the performance of SMEs in the location of the city of Salatiga does not yet exist for this relationship.